AIDS and discrimination: Points of view of a group of adolescents and persons that live with the human immune-deficiency virus. - Ana María Molina Gómez; Yuniet Rojas Mesa; Jorge García Cuesta; María Elinor Dulzaides Iglesias; Oristela Mora Rodríguez (Medisur)
Background: Since the beginnings of the Infection with HIV, mankind has been greatly concerned. This disease emerged with a series of stigmata, injuring personal integrity of those who suffer from it. Methods: A descriptive study made in Cienfuegos, in which 120 adolescents and 29 PVHIV were inquired and also conferences about this illness were given. Results and Conclusions: The 120 inquired affirmed they knew about the disease and was receiving information regarding it. The majority identifies blood, vaginal secretions, semen, sharing contaminated needles and syringes as main ways of transmission, they also consider that keeping a stable mate friend is the best way to protect themselves. The 50,8% think the names of the infected should be informed to population, and the 15,% is worried about sharing their working or scholar life with them. The 26% think the infected people should live isolated in a sanatorium. On the other hand, 16 PVHIV said they have felt sometimes discriminated, and 11 stated that at the time of asking for medical help, the personnel have attended them in a despicable manner. 3 of them felt the familiar rejection, and 7 stated that the community and his very friends were getting away from them.